2012
DOI: 10.1089/gtmb.2011.0315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Glutathione S-Transferase P1 Polymorphisms (Ile105Val and Ala114Val) in Patients with Small Cell Lung Cancer

Abstract: The variant GSTP1 exon 6 genotype might be conferring protection against SCLC development. Whether this effect is associated with exposure to cigarette smoking needs to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Moreover, the single nucleotide polymorphism at the GSTP1 loci results in an amino acid substitution that leads to reduced activity, which may alter susceptibility to cancer. Since Harris et al (1998) first examined the association between the GSTP1 341C/T polymorphism and the risk of lung cancer, a number of other studies have been conducted to evaluate the role of the 341C/T polymorphism in the GSTP1 gene on lung cancer risk (Wang et al, 2003;Yang et al, 2004;Zienolddiny et al, 2008;Vural et al, 2012). However, the results remain conflicting rather than conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the single nucleotide polymorphism at the GSTP1 loci results in an amino acid substitution that leads to reduced activity, which may alter susceptibility to cancer. Since Harris et al (1998) first examined the association between the GSTP1 341C/T polymorphism and the risk of lung cancer, a number of other studies have been conducted to evaluate the role of the 341C/T polymorphism in the GSTP1 gene on lung cancer risk (Wang et al, 2003;Yang et al, 2004;Zienolddiny et al, 2008;Vural et al, 2012). However, the results remain conflicting rather than conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Through screening the title and reading the abstract/article, 5 eligible articles were selected for this meta-analysis (Harris et al, 1998;Wang et al, 2003;Yang et al, 2004;Zienolddiny et al, 2008;Vural et al, 2012). The detailed screening process is shown in Figure 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The polymorphisms in GSTM1 and GSTT1 have been investigated in cancer for a long time; however, only recently have some studies investigated the association of various cancers with GSTP1 variants. Some studies have observed a different relation between the GSTP1 polymorphism and an increased risk for oral [17], breast [15], [18], colorectal [19], prostate [20] and lung [21], [22] cancers. Regarding gastric cancer, only a few studies were conducted to investigate its association with GSTP1 variants [23].…”
Section: Introductionmentioning
confidence: 99%
“…This group did not provide evidence for a strong association between GSTP1 rs1138272 and lung cancer susceptibility (Ye et al, 2006). Yan et al (2016) included five case-control studies (Harris et al, 1998; Wang et al, 2003; Yang et al, 2004; Zienolddiny et al, 2008; Vural et al, 2012) to perform another relative meta-analysis (Yan et al, 2016) wherein an association between GSTP1 rs1138272 and increased lung cancer risk was detected (Yan et al, 2016). Here, in our subgroup analysis of lung cancer, we removed one study that was not in HWE (Vural et al, 2012) and added two case-control studies (Saarikoski et al, 1998; Minina et al, 2017) for the pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al (2016) included five case-control studies (Harris et al, 1998; Wang et al, 2003; Yang et al, 2004; Zienolddiny et al, 2008; Vural et al, 2012) to perform another relative meta-analysis (Yan et al, 2016) wherein an association between GSTP1 rs1138272 and increased lung cancer risk was detected (Yan et al, 2016). Here, in our subgroup analysis of lung cancer, we removed one study that was not in HWE (Vural et al, 2012) and added two case-control studies (Saarikoski et al, 1998; Minina et al, 2017) for the pooled analysis. Based on the available data within seven articles (Harris et al, 1998; Saarikoski et al, 1998; Wang et al, 2003; Sorensen et al, 2004; Yang et al, 2004; Zienolddiny et al, 2008; Minina et al, 2017), we failed to detect a relationship between GSTP1 rs1138272 and lung cancer risk in the overall population.…”
Section: Discussionmentioning
confidence: 99%